Palmitic Acid Inhibits the Virulence Factors of Candida tropicalis: Biofilms, Cell Surface Hydrophobicity, Ergosterol Biosynthesis, and Enzymatic Activity - Prasath, Krishnan Ganesh; Tharani, Hariharan; Kumar, Mourya Suraj; Pandian, Shunmugiah Karutha (Frontiers in Microbiology, 2020)
Biofilm is the fortitude of Candida species infections which eventually causes candidiasis in human. C. tropicalis is one of the predominant Candida species commonly found in systemic infections, next to C. albicans. In Candida species, biofilm maturity initiates irreversible surface attachment of cells and barricades the penetration of conventional antifungals. Hence, the current study investigated the antifungal and antivirulence potency of palmitic acid (PA) against C. tropicalis mature biofilm and its associated virulence factors. In vitro results revealed an effective inhibition of biofilm in PA-treated C. tropicalis, compared to C. albicans and C. glabrata. Also, PA reduced C. tropicalis mature biofilm at various time points. Further, PA treatment triggered apoptosis in C. tropicalis through ROS mediated mitochondrial dysfunction as demonstrated by confocal microscopic observation of PI, DAPI and DCFDA staining. PA regulated other virulence factors such as cell surface hydrophobicity, ergosterol biosynthesis, protease and lipase after 48 h of treatment. Downregulation of ERG11 (Lanosterol 14-alpha demethylase) was contributed to the reduction of ergosterol in PA-treated C. tropicalis. However, enhanced hyphal growth was observed in PA-treated C. tropicalis through upregulation HWP1 (Hyphal wall protein) and EFG1 (Enhanced filamentous growth). This study highlighted the antibiofilm and antivirulence potency of PA against C. tropicalis. Hence, PA could be applied synergistically with other antifungal agents to increase the efficacy for regulating NCAC infections.